Methane production from anaerobic co-digestion of sewage sludge and decanter cake - Khairul Anuar, Norshafiqah (2021)
Increased production of sewage sludge from wastewater treatment and decanter cake from palm oil mill industry results in the generation of large quantities of solid waste. These wastes can cause environmental pollution and can give bad impact on human lifestyle. Sewage sludge can produce methane gas at a very minimum rate of production. Co-digestion with decanter cake which content high of carbon can increase methane gas production. In this research, an anaerobic co-digestion has been considered to convert these organic pollutants into methane gas. The preliminary study was set up to optimized the ratio of sewage sludge (as inoculum) and decanter cake (as substrate) in batch biochemical methane potential (BMP) in serum bottle of 125 mL volume for 30 days. The effect of different inoculum to substrate ratios (I/S) on biogas production was investigated at mesophilic condition (38 ± 1 °C) and constant initial pH 7. The batch study was conducted at the ratio I/S of 2:1, ratio 1:1 and ratio 1:2 and sewage sludge only as control experiment. The preliminary study resulted in daily biogas collection for the ratio of 1:2 showed the highest cumulative biogas production of 247 mL. Total solid content and ammonia removal had been compared at initial and final fermentation in the biochemical methane potential (BMP) batch fermentation. The highest methane yield was obtained at the mixing ratio of 2:1 with 165.6 mL CH4/g VS and this ratio had been choose to be the best I/S ratio from BMP test. Then the ratio of 2:1 is upscale into a lab-scale anaerobic digester to determine the maximum production of methane gas. 6.4L of anaerobic digester has been used with 5.6L of the working volume and was fermented for 30 days. Cumulative biogas production resulted in 5848 mL and cumulative methane gas production resulted in 10451 mL CH4/g VS. Theoretically, biogas is mainly composed of methane (60 %) and carbon dioxide (40 %) as of end product of anaerobic digestion. These were compared for all ratios and resulted significantly as theoretical. The experimental value of methane yield from lab-scale anaerobic digester then compared with the theoretical value of methane yield by using the Gompertz equation solve in Excel Solver. As a comparison, all co-digestion ratios produced more biogas than the sewage sludge alone. This proved that anaerobic co-digestion of sewage sludge and decanter cake can improve the production of biogas.